International Encounters: Higher Education and the International Student Experience - Gargano, Terra (Journal of International Students, 2020)
Throughout International Encounters: Higher Education and the International Student Experience, the authors encourage faculty, program administrators, and institutional leaders to challenge the deficient model that is often associated with international student experiences, and instead employ those in higher education to recognize the human, social, mobility, cultural, and identity capital that international students bring to universities and colleges. The editors are to be applauded for the unpacking and problematizing of terms such as “foreign student,” “cosmopolitanism,” “foreignness,” and “international” and for recognizing the assemblance of international education research and literature as somewhat haphazard, although prolific.